The Correlation between Self-Confidence and Students’ English Achievement of Tertiary Students at Universitas Advent Indonesia - Marpaung, Marlin Steffi (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2018)
Self-confidence is one of the important factors in determine students’ English achievement. This study aims to find out the correlation between self-confidence and students’ English achievement and to answer the question of the hypothesis there is a correlation between self-confidence and students’ English achievement. The sample of this study were 30 tertiary students of English Language Education study program at Universitas Advent Indonesia. A questionnaire was used to gather the data, the questionnaire consisted of 20 questions and used the five-point Likert scale. The questionnaire was given to the students to measure their self-confidence and then correlated the questionnaire result with the students’ English achievement grade. Spearman’s Coefficient of (Rank) correlation was used in order to answer the question of the correlation between self-confidence and the students’ English achievement and the data was calculated using SPSS. The result showed that there is no significant correlation between self-confidence and students’ English achievement. However, since there is no enough evidence, they cannot be rejected. For future researchers, it is recommended to do another study with enough data and evidence with different levels of students and different aspect of English skills such as speaking. Keyword: Self-confidence, English Achievement, tertiary students